L2, H2 Guaranteed-Cost Control of LPV Systems with Saturating Actuators - Delibasi, Akin; Kucukdemiral, Ibrahim B.; Cansever, Galip (IEEE, 2008)
The design problem of mixed L-2, H-2 gain scheduling nonlinear state feedback controller for Linear Parameter Varying (LPV) systems subjected to actuator saturations and L-2 bounded disturbances is considered. First, a new formulation of H-2 controllers has been presented based on the Homogeneous Polynomial Parameter Dependent (HPPD) representation. Then a systematic procedure to generate a sequence of LMI conditions of increasing precision for obtaining a sub-optimal L-2, H-2 state-feedback controller for LPV systems subject to actuator saturations and L-2-bounded disturbances, has been presented. The presented method utilizes the modified sector condition for actuator saturation formalization and HPPD representation of LPV systems.
Keywords: LINEAR-SYSTEMS; STATE-FEEDBACK; STABILITY; COMPUTATION; H2; Automation & Control Systems